Risk factors of Arterial Hypertension in Adolescents - Raidel González Rodríguez (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
By means of the National Program for Preventing, Diagnosing, Evaluating and Controlling, Cuba of arterial hypertension has tried to provide Primary Health Care with an effective tool to train family doctors and nurses in fighting for prevention in adolescence in a practical, timely and efficient way. But it should not only be the responsibility of this care level but also of institutions, political and mass organisms, so as family and community members.